2013
DOI: 10.3311/ppch.2175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of additive and reactive phosphorus-based flame retardants in epoxy resins

Abstract: The aim of this work was to investigate the effect of phosphorus-based additive and reactive flame retardants (FR) on the flammability and mechanical properties of a pentaerythritol-based model epoxy resin system cured with a cycloaliphatic diamine hardener. Commercially available ammonium polyphosphate (APP) was used as additive and 9,10-dihydro-9-oxa-10-phosphaphenantrene-10-oxide IntroductionEpoxy resins are extensively used in various industrial application fields as, for example, adhesives, surface coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…The P-content of the flame retarded matrix was chosen to be 2.5 mass%, to reach V-0 rating in UL-94 tests, according to previous studies of the authors [19,28] …”
Section: Flame Retardancy Of the Compositesmentioning
confidence: 99%
“…The P-content of the flame retarded matrix was chosen to be 2.5 mass%, to reach V-0 rating in UL-94 tests, according to previous studies of the authors [19,28] …”
Section: Flame Retardancy Of the Compositesmentioning
confidence: 99%
“…The covalent bonding brought by the reactive approach could favor the charring effect. Recently, Szolnoki et al [16] reported a study which compares the additive approach to the reactive one in epoxy thermoset using a phosphorus-containing diamine (curing agent) as reactive P-FR and the ammonium polyphosphate as additive P-FR, showing that a lower phosphorus content is required to reach the V-0 grade at UL-94 test by the reactive approach. However, the P-FR systems used possess different chemical structures which can influence the results.…”
Section: Introductionmentioning
confidence: 97%
“…In parallel with the continually increasing use of plastics, the issue of fire safety has come to the forefront. Flame retardancy of polymers has become essential in many application fields such as transportation, construction, and electrical industries [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%